STRATEGY FOR IMPROVING THE PERFORMANCE OF EDUCATIONAL PERSONNEL IN THE FACULTY OF DENTISTRY, UNIVERSITY OF NORTH SUMATRA - Annisa Ika Savira; Iskandarini; Prihatin Lumbanraja (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The performance of educational staff plays a strategic role in supporting the quality of academic services and university governance. The Faculty of Dentistry, University of North Sumatra (FKG USU) is required to improve the performance of educational staff in line with the implementation of the BINTANG values as the institution's work culture. However, the results of the pre-survey and data from the FKG USU Sub-HRD for the 2023–2024 period indicate that the performance of educational staff tends to stagnate and the implementation of BINTANG values has not been optimal. This study aims to analyze the implementation of BINTANG values in the work behavior of educational staff and formulate performance improvement strategies based on the SOAR (Strengths, Opportunities, Aspirations, Results) approach. This study used a qualitative descriptive method conducted at FKG USU from June–November 2025, involving 15 informants selected purposively. Data collection was carried out through in-depth interviews, observation, documentation, and open-ended questionnaires. The results of the study indicate that BINTANG values have been reflected in the work ethic of educational staff, especially in the aspects of integrity, discipline, commitment to service, and cooperation, although they still need to be strengthened. The SOAR analysis resulted in a performance improvement strategy that emphasizes strengthening leadership with integrity, developing human resource competencies, internalizing BINTANG values, and implementing a sustainable performance-based reward system.